The Influence of Distributor Competence, Informational Sharing on Distribution Performance: The Role of Distributional Commitment - Atjas, Bernadus; Sitaniapessy, Rainier Hendrik (SEAN Institute, 2024)
This study began with the differences in research results on the relationship between distributor competence and distributor performance. By using the theory of resource advantage, we developed distributional commitment as a way to overcome this gap. The sample used was 115 respondents using non-probability sampling techniques and Structural Equation Modeling analysis techniques. The results of the study explain that distributor competence, information sharing has a significant effect on distributional commitment which ultimately has a significant effect on distributor channel performance.